Превентивное оценивание эффективности финансового управления на предприятии - Мищенко, Владимир Акимович; Ситак, Ирина Леонидовна; Домнина, Ирина Игоревна (Premier Publishing s.r.o., Vienna, 2020)
Describes the need in the current environment to improve the quality of general and financial management in the enterprise. A methodical approach to the calculation of the index of financial management efficiency taking into account internal factors and stock market indicators is proposed. The dynamics of this index over time can be used for self-management at management levels to improve the quality of this process.

Описывается необходимость в нынешних условиях повышения качества общего и финансового управления на предприятии. Предложен методический подход к расчету индекса эффективности финансового управления на основе внутренних факторов и биржевых индикаторов. Динамика этого индекса во времени может быть использована для самоменеджмента на управленческих уровнях с целью повышения качества этого процесса.
Preventive evaluation of the effectiveness of financial management in the enterprise
Keywords: financial management; invested capital; property asset; net income; profitability of capital; economic valueadded; spread; bankruptcy; финансовое управление; инвестированный капитал; собственный капитал; чистая прибыль; рентабельность капитала; экономическая добавленная стоимость; спрэд; банкротство